On the Kisceral Mode of Argumentation - Tindale, Christopher (Informal Logic)

(untitled) (Informal Logic, 2022)
Of the different modes that characterize Michael Gilbert’s multi-modal theory of argumentation, the kisceral is in many ways the most challenging to understand and employ. It appears to bypass the processes of reason that have dominated accounts in the Western tradition, diverting us toward the private worlds of hunches and gut reactions. This paper explores the nature of kisceral arguments, comparing them to the way intuition operates in William James’ examination of mystical experience. Having provided an account of kisceral arguments and their operation, the discussion turns to the even more challenging issue of how such arguments should be evaluated.